2021
DOI: 10.3390/molecules26071824
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized Whey Protein Concentrate-Based Glutathione Delivery System: Physicochemical Characterization, Bioavailability and Sub-Chronic Toxicity Evaluation

Abstract: Glutathione (GSH) is a powerful antioxidant, but its application is limited due to poor storage stability and low bioavailability. A novel nutrient encapsulation and delivery system, consisting of polymerized whey protein concentrate and GSH, was prepared and in vivo bioavailability, antioxidant capacity and toxicity were evaluated. Polymerized whey protein concentrate encapsulated GSH (PWPC-GSH) showed a diameter of roughly 1115 ± 7.07 nm (D50) and zeta potential of 30.37 ± 0.75 mV. Differential scanning calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The low peak temperature in the exothermic transitions of SGWP when compared to SG1 was due to the presence of 6.5% w/v of SG along with WPI. These observations indicated that an increase in the concentrations of SG and WPI in the hydrogel would enhance self‐association (aggregation) of thermally denatured whey protein (Zhang et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The low peak temperature in the exothermic transitions of SGWP when compared to SG1 was due to the presence of 6.5% w/v of SG along with WPI. These observations indicated that an increase in the concentrations of SG and WPI in the hydrogel would enhance self‐association (aggregation) of thermally denatured whey protein (Zhang et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…PU/GSH//GelMA/Ker dressing exhibited relatively weak antioxidant activity, which was attributed to the introduced GSH, gelatin, and keratin, all of which possessed reducibility. [57][58][59] As a predominant antioxidant, GSH maintains intracellular redox homeostasis by consuming oxidizing substances such as ROS. 60 When KTC was added in place of keratin, the antioxidant activity of the PU/GSH// GelMA/KTC dressing was greatly enhanced, which was attributed to the sustained release of H 2 S. All these results confirmed that PU/ GSH//GelMA/KTC dressing possessed the good anti-oxidant ability.…”
Section: Antioxidant Abilitymentioning
confidence: 99%
“…The following four contributions [ 15 , 16 , 17 , 18 ] present selected interventions which modulate the GSH/GSSG system. One of the contributions of this session [ 15 ] describes a new HPLC/DAD method to quantify the reduced glutathione (GSH) and oxidized glutathione (GSSG) levels in rat brain.…”
mentioning
confidence: 99%